Population abundance, density and diversity of antelope species in pandam wiildlife park, plateau state, Nigeria (2022)
Habitat loss and fragmentation are heating deep into conservation areas like Wildlife Parks and this has posed a serious threat to wildlife population abundance and diversity. The fluctuations in population of fauna species are dependent on the quality of the habitat. Therefore, the population abundance, density and diversity of antelope species were investigated. Line transects (2 km each) were laid 1km apart in: savannah woodland-SW (n=4), riparian forest -RF (n=3) and swamp land-SL (n=3). The line transect method was used to identify antelopes during wet (July-October) and dry (December-March) seasons (2017-2019). Simpson’s (D) and Shannon-Weiner (H’) indices were estimated for herbivores. Data were analysed using descriptive statistics and ANOVA at α0.05. Four Antelopes were identified and Kobus kob was most dominant. Antelope abundance and mean population density increased from SL (18, 2.3) to SW (80, 10) and were higher in dry (70, 8.8) than wet (56, 7.0) season. Antelopes, highest D (0.7) and H’ (1.6) were in SW, while least were in SL (D= 0.6, H’= 1.2). The savannah woodland favoured the antelopes and had influence on their abundance and diversity. Antelope species were almost not found in other habitats due to human activities within the park. The anthropogenic activities are fast entering into the core area of the park. Hence, the park management should take strategic measures to curb this fast-rising challenges.